Description of a cryptic new species of Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the Western Ghats of Kerala State of India - Sayyed, Amit; Grismer, L. Lee; Campbell, Patrick D; Dileepkumar, Raveendran (Zootaxa, 2019)
We describe a cryptic new species of gecko of the genus Cnemaspis Strauch from the southern Western Ghats of Kerala. This medium-sized Cnemaspis species is differentiated from all other Indian congeners by a suite of the following distinct morphological characters: heterogeneous mid-dorsal scales, 6–7 supralabials; 113–120 paravertebral rows of tubercles; 71–85 mid-dorsal scales; absence of spine-like tubercles on flanks; subimbricate, smooth ventral scales; 135–140 mid-ventral scales; subdigital lamellae under fourth digit of manus 23–25; subdigital lamellae under fourth digit of pes 24–25; males with 7–8 precloacal pores; median row of subcaudals enlarged, smooth, a series of two large scales alternating, containing one divided scale; head and neck colouration brownish-yellow, consistent in adult males; adult females with orange coloured head and neck. Recent new descriptions of Cnemaspis species together with the present discovery show that the southern Western Ghats species have been overlooked by previous studies. Therefore we suggest further studies to evaluate the diversity of Cnemaspis in this region.